all equations that the type ax^2+bx+c=0 can be addressed using the quadratic formula: frac-b±sqrtb^2-4ac2a. The quadratic formula gives two solutions, one when ± is enhancement and one once it is subtraction.

You are watching: Solve x2 + 6x + 4 = 0.


This equation is in typical form: ax^2+bx+c=0. Substitute 1 because that a, -6 because that b, and -4 for c in the quadratic formula, frac-b±sqrtb^2-4ac2a.
*

displaystylex=3+sqrt13,3-sqrt13 Explanation: displaystylex^x-6x-4=0 completing the square method that us will force a perfect square trinomial top top the left ...
(2x2)-(6x)-4=0 Two services were discovered : x =(3-√17)/2=-0.562 x =(3+√17)/2= 3.562 action by action solution : action 1 :Equation in ~ the end of step 1 : (2x2 - 6x) - 4 = 0 step 2 : step 3 ...
3x2-6x-4=0 Two remedies were discovered : x =(6-√84)/6=1-1/3√ 21 = -0.528 x =(6+√84)/6=1+1/3√ 21 = 2.528 step by action solution : step 1 :Equation in ~ the finish of step 1 : (3x2 - 6x) - 4 = 0 ...
The root aredisplaystylefrac3+sqrt295ordisplaystylefrac3-sqrt295 .Explanation: displaystylex=frac-b±sqrtb^2-4ac2a ...
9x2-6x-4=0 Two remedies were found : x =(6-√180)/18=(1-√ 5 )/3= -0.412 x =(6+√180)/18=(1+√ 5 )/3= 1.079 step by step solution : action 1 :Equation at the end of action 1 : (32x2 - 6x) - 4 = ...
18x2-6x-4=0 Two remedies were discovered : x = -1/3 = -0.333 x = 2/3 = 0.667 action by action solution : step 1 :Equation in ~ the end of step 1 : ((2•32x2) - 6x) - 4 = 0 step 2 : step 3 ...
More Items
*
*

*
*
*

All equations of the type ax^2+bx+c=0 deserve to be resolved using the quadratic formula: frac-b±sqrtb^2-4ac2a. The quadratic formula offers two solutions, one as soon as ± is enhancement and one when it is subtraction.
This equation is in typical form: ax^2+bx+c=0. Substitute 1 because that a, -6 because that b, and also -4 because that c in the quadratic formula, frac-b±sqrtb^2-4ac2a.
Quadratic equations such together this one can be resolved by perfect the square. In stimulate to finish the square, the equation must very first be in the form x^2+bx=c.
Divide -6, the coefficient that the x term, through 2 to get -3. Then include the square the -3 to both sides of the equation. This step provides the left hand next of the equation a perfect square.
Factor x^2-6x+9. In general, once x^2+bx+c is a perfect square, that can always be factored as left(x+fracb2 ight)^2.

See more: What Is The Final Step When Constructing A Briefing ? What Is The Final Step Constructing A Briefing


Quadratic equations such as this one have the right to be addressed by a brand-new direct factoring an approach that walk not call for guess work. To use the direct factoring method, the equation have to be in the type x^2+Bx+C=0.
Let r and also s it is in the components for the quadratic equation such that x^2+Bx+C=(x−r)(x−s) where amount of components (r+s)=−B and the product of components rs = C
Two number r and s amount up to 6 precisely when the average of the 2 numbers is frac12*6 = 3. Friend can likewise see that the midpoint the r and s corresponds to the axis of the opposite of the parabola stood for by the quadratic equation y=x^2+Bx+C. The values of r and s room equidistant native the center by one unknown amount u. Refer r and also s v respect to change u.
*
*

EnglishDeutschEspañolFrançaisItalianoPortuguêsРусский简体中文繁體中文Bahasa MelayuBahasa Indonesiaالعربية日本語TürkçePolskiעבריתČeštinaNederlandsMagyar Nyelv한국어SlovenčinaไทยελληνικάRomânăTiếng Việtहिन्दीঅসমীয়াবাংলাગુજરાતીಕನ್ನಡकोंकणीമലയാളംमराठीଓଡ଼ିଆਪੰਜਾਬੀதமிழ்తెలుగు